METHODICAL APPROACH TO CLUSTERING OF REGIONS OF CHINA BY THE DEGREE OF MANIFESTATION OF COMPETITIVE ADVANTAGES - Zeyu, Liu (Bulletin of Sumy National Agrarian University, 2023)
The article proposes clustering, the essence of which is to group the regions of China on the basis of the degree of manifestation of their competitive advantages by technological-innovative, educational-intellectual, economic-infrastructural, tourist-cultural groups. The methodical approach of permits to assess territories is not only from the side of administrative division, it identifies specific territories that may have similar marketing management strategies in order to achieve a high degree of competitive advantage and affect the competitiveness of the region as a whole. Management of competitive advantages of regions, taking into account the cluster approach, allows not only to assess the current situation to a more complete and specific extent, but also to effectively use the resources necessary for harmonious development. The application of the cluster approach in the coordination of the activities of territories will create a high-quality competitive territorial brand that will have positive consequences in the social, economic and other spheres of society.